RISK FACTORS OF CHRONIC KIDNEY DISEASE AMONG PATIENTS ATTENDING IBN SINA TEACHING HOSPITAL IN MOSUL CITY (Iraqi Journal of Medical Sciences, 2019)
Background: Chronic kidney disease (CKD) is a long-term health condition that in many cases is preventable. Many people do not know they have kidney disease, because up to 90% of kidney function can be lost before symptoms are evident. Fortunately, simple tests performed by a general practitioner can identify most cases of CKD when the disease is in its early stages, enabling treatment to prevent or slow progress.Objective: To evaluate the risk factors for the development of CKD.Methods: A case-control study conducted to 300 persons (150 cases and 150 controls) selected from Medical Wards, Dialysis Kidney Unit and in Outpatient Clinic at Ibn Sina Teaching Hospital in Mosul City.Results: Diabetes mellitus (DM) had 12.9 folds risk for developing of CKD and both type 1 and type 2 D.M. had significant role for developing CKD. Diabetic patients for (> 15 years) had 29.8 times risk for development of CKD. Hypertension (HT) had 3.5 folds risk for CKD and those having HT more than 15 years had 12.9 times risk for CKD. Cardiovascular disease (CVD) had 13.6 folds risk for CKD and having more than one type of CVD had 37 times risk for CKD than heart failure, ischemic heart disease. Family history of renal diseases had 7.1 times risk for CKD and there was statistically significant role of having family history of CKD that had more than 22 times risk for CKD. Statistically significant role of having proteinuria with 383 times risk for CKD.Conclusion: There are many risk factors significantly contributing to the development of CKD in Mosul especially DM, HT, CVD, family history of renal disease, family history of chronic diseases, and from this study it has been concluded that proteinuria plays a major role for the development and progress of CKD.Keywords: Chronic kidney disease, risk factorsCitation: Khaleel FF, Hussain SS, Hmood AH. Risk factors of chronic kidney disease among patients attending Ibn Sina Teaching Hospital in Mosul City. Iraqi JMS. 2019; 17(1): 24-31. doi: 10.22578/IJMS.17.1.5
Keywords: Chronic kidney disease; risk factors